Systematic identification of the protein substrates of UDP‐GalNAc:polypeptide N‐acetylgalactosaminyltransferase‐T1/T2/T3 using a human proteome microarray. Issue 11 (8th June 2017) - Xu, Zhijue; Li, Xing; Zhou, Shumin; Xie, Wenxian; Wang, Jing; Cheng, Li; Wang, Sheng; Guo, Shujuan; Xu, Zhaowei; Cao, Xin; Zhang, Menghui; Yu, Biao; et al.
Abstract : O ‐GalNAc glycosylation is the initial step of the mucin‐type O ‐glycosylation. In humans, it is catalyzed by a family of 20 homologous UDP‐GalNAc:polypeptide N‐acetylgalactosaminyltransferases (ppGalNAc‐Ts). So far, there is very limited information on their protein substrate specificities. In this study, we developed an on‐chip ppGalNAc‐Ts assay that could rapidly and systematically identify the protein substrates of each ppGalNAc‐T. In detail, we utilized a human proteome microarray as the protein substrates and UDP‐GalNAz as the nucleotide sugar donor for click chemistry detection. From a total of 16 368 human proteins, we identified 570 potential substrates of ppGalNAc‐T1, T2, and T3. Among them, 128 substrates were overlapped, while the rest were isoform specific. Further cluster analysis of these substrates showed that the substrates of ppGalNAc‐T1 had a closer phylogenetic relationship with that of ppGalNAc‐T3 compared with ppGalNAc‐T2, which was consistent with the topology of the phylogenetic tree of these ppGalNAc‐Ts. Taken together, our microarray‐based enzymatic assay comprehensively reveals the substrate profile of the ppGalNAc‐T1, T2, and T3, which not only provides a plausible explanation for their partial functional redundancy as reported, but clearly implies some specialized roles of each enzyme in different biological processes.